External validation of sTWEAK as a prognostic noninvasive biomarker for head and neck squamous cell carcinoma. (17th December 2015) - Terra, Ximena; Gómez, David; García‐Lorenzo, Jacinto; Flores, Joan Carles; Figuerola, Enric; Mora, Josefina; Chacón, Matilde R.; Quer, Miquel; Camacho, Mercedes; León, Xavier; Avilés–Jurado, Francesc Xavier
Abstract: Background: The main purpose of this study was to validate the prognostic significance of tumor necrosis factor (TNF)‐like weak inducer of apoptosis (TWEAK) in head and neck squamous cell carcinoma (HNSCC) using an independent cohort. Methods: Data were evaluated from 153 patients with HNSCC in stages III to IV, who received radiotherapy (RT) or chemoradiotherapy. We quantified soluble TWEAK (sTWEAK) in pretreatment samples using enzyme‐linked immunosorbent assay. Results: The classification tree revealed a cutoff value of 322 pg/mL for sTWEAK to be ideal for discriminating between patients' disease control. Kaplan–Meier curves indicate that the disease‐free survival rate in patients with high sTWEAK was significantly higher than in patients with low levels ( p = .006, log‐rank test). An independent link was identified between low sTWEAK and poor clinical outcome in Cox regression multivariate analysis (hazard ratio = 1.866; 95% confidence interval [CI] = 1.114–3.125; p = .001). Conclusion: Our study highlights the significance of this noninvasive biomarker in the discrimination according to the disease control achieved by patients who received a nonsurgical organ‐preservation treatment. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1358–E1363, 2016